Edukasi Penanganan Cidera Acute pada Komunitas Olahraga Cerebral Palsy Football di National Paralympic Committee Indonesia - Suryo Saputra Perdana; Wahyu Tri Sudaryanto; Aulia Rahman; Navisatul Oktaviana; Rahma Alfina (Jurnal Pengabdian Masyarakat, 2023)
Football is a body contact sport that can cause injury during a match. CP football athletes at NPCI already have good performance but the level of knowledge related to how to handle acute injuries is still low. The purpose of this service activity is to increase the level of knowledge related to handling acute injuries in the CP football sports community at NPCI. This activity was attended by 14 athletes who were carried out offline at Manahan Stadium with lecture methods and leaflet media. Evaluation of knowledge about handling acute injuries using the RICE method using a questionnaire distributed via google form both before and after the material delivery process. The pre-test results obtained as many as 6 athletes (42.9%) were in the sufficient category regarding understanding of the handling of acute injuries by the RICE method and 8 athletes (57.1%) had a good understanding. From the post-test results, 7 athletes (50%) have knowledge in the good category and 7 athletes (50%) have knowledge in the excellent category. After being given education and direct demonstration, there was an increase in knowledge about handling acute injuries with the RICE method in the CP football sports community at NPCI.